Developmental regression of novel space preference in an autism spectrum disorder model is unlinked to GABAergic and social circuitry - Asano, Hirofumi; Arai, Masaya; Narita, Aito; Kuroiwa, Takayuki; Fukuchi, Mamoru; Yoshimoto, Yuhei; Oya, Soichi; Miyoshi, Goichi (Frontiers in Cellular Neuroscience, 2025)
Autism spectrum disorder (ASD) is characterized by social deficits and restricted behaviors, with developmental defects in GABAergic circuits proposed as a key underlying etiology. Here, we introduce the V-Y assay, a novel space preference test in which one arm of the Y-maze is initially hidden and later revealed as a novel space. Using an ASD mouse model with FOXG1 haploinsufficiency, which exhibits ASD-like social impairments that can be either exacerbated or ameliorated by GABAergic circuit manipulations, we observed impaired novel space preference and exploratory behavior in the V-Y assay. Interestingly, unlike social phenotypes, novel space preference was initially established by 3 weeks of age but regressed by 6 weeks. Furthermore, alterations in GABAergic signaling via Gad2 mutation did not affect novel space preference, in contrast to their impact on social behaviors. These findings reveal that the regression of novel space preference in ASD follows a distinct developmental trajectory from GABA-driven social impairments, providing new insights into the mechanisms underlying ASD.